Computational Fluid Dynamic Analysis in Spray Dryer Design By Distillation System Of Sea Water To Salt - Ibnu Irawan; Rifky Yusron (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Spray Dryer is the most widely used industrial process for drying. Continuous production can be carried out in powder or powder form from liquid raw materials. The feed to some desiccant may be a liquid in which the solid will float as light particles, or it may be in the form of a solution. Some drying products are resistant to rough handling and very hot environments, but some require careful handling at low or moderate temperatures. Computational Fluid Dynamics (CFD) in a spray dryer system design uses an atomization system to convert seawater into salt. The process of analyzing several needs, regarding the function of time from worker efficiency and the results of processing seawater into salt is the focus of researchers. The results of this research process are CFD analysis on spray dryer system design, analysis of mass flow rate and heat of drying air. The results from the analysis using CFD can be concluded, namely the spray dryer design specifications are __ = 1500 mm __ = 200 mm, diameter = 1100 mm. While the temperature of the hot air entering is 130oC and the pressure to the nozzle is 12.849 psi. The Spray Dryer as a result of the design planning is capable of producing 0.36 kg salt/hour with a seawater requirement of 10.25 kg. The results of the simulation of the inflow of hot air fluid and seawater spray on the nozzle, show the level of homogeneity of the mixture, this can cause seawater particles to separate, one of which is NaCl or salt. System efficiency is at 80% based on the mass of seawater processed to become salt.